Proline/arginine dipeptide repeat polymers derail protein folding in amyotrophic lateral sclerosis - Maria Babu (Nature Portfolio, 2021)
The most frequent cause of familial Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Dementia (FTD) are hexanucleotide repeat expansions in the non-coding region of the C9ORF72 gene that are translated into five dipeptide repeat (DPR) proteins. Here, the authors show that proline/arginine (PR) DPRs inhibit the prolyl isomerase PPIA and reveal the molecular mechanism of the impaired protein folding activity of PPIA by performing NMR measurements and determining a PR DPR bound PPIA crystal structure.